Weather conditions of fog at the airport in Almaty and their impact on aviation (Journal of Geography and Environmental Management, 2016)
This article describes the meteorological characteristics of fog at the airport in Almaty for the periods 1998-2007, 2010-2012. Calculated statistics mists, as well as repeatability of meteorological variables (relative humidity, air temperature, wind speed and direction) in the mists. The data on the frequency and duration of fog, the first and last dates of the fog. Selected special cases the longest continuous fog and analyzed maps of surface analysis and AT-500. For consideration regime Almaty airport in bad weather conditions examined data on the interrupted flights passenger aircraft at the airport as a result of adverse weather in 2008-2012. It is concluded that the impact on the fog mode Almaty airport.
Keywords: fog; repeatability; weather conditions